Genderqueer and non-binary genders - Richards, Christina; Bouman, Walter Pierre; Barker, Meg-John, 1974- (Critical and applied approaches in sexuality, gender and identity., 2017)
This book addresses the emerging field of genderqueer or non-binary genders - that is, individuals who do not identify as male or female. It considers theoretical, research, practice, and activist perspectives; and outlines a basis for good practice when working with non-binary individuals. The first section provides an overview of historical, legal and academic aspects of this phenomenon. The second section explores how psychotherapeutic, psychological and psychiatric theory and practice are adapting to a non-binary model of gender, and the third section considers the body related aspects, from endocrinology to surgery. This work will appeal to a wide readership, from practitioners working with non-binary individuals - including psychologists, surgeons, social workers, nurses, psychiatrists, endocrinologists, psychotherapists and counselors, lawyers, and healthcare workers - to researchers interested in the study of gender identities, to students and gender activists.